Etiological profile and outcome and hypertransaminemia in children - Dr. Janani Sankar; Dr. Venkateswari Ramesh; Nagamalleswari (Pediatric Review: International Journal of Pediatric Research, 2018)
Objectives: To study the causes of elevated transaminases in children and assess their outcome. Material and Methods: Retrospective study conducted at Kanchi Kamakoti CHILDS trust hospital, Chennai for 6 months. Medical records of 305children with hypertransaminemia were analyzed for identifying etiology, their utility in diagnosis as well as predicting outcome. Results: The commonest etiology of elevated transaminases were infections. Highest levels of elevation were recorded in drug induced liver injury and shock. Massive elevation of transaminases along with deranged prothrombin time and albumin was associated with greater mortality and morbidity. Conclusions: Serum transaminases may be adapted as an improtant investigation, not only to detect liver dysfunction but also to diagnose and prognosticate several disaeses which are non-hepatic in origin.